Epidemics : The Story of South Africa's Five Most Lethal Human Diseases - Phillips, H. (Howard), 1949- (Book collections on Project MUSE., 2012)
"This is the first history of epidemics in South Africa, lethal episodes that significantly shaped this society over three centuries. Focusing on five devastating diseases between 1713 and today--smallpox, bubonic plague, "Spanish influenza," polio, and HIV/AIDS--the book probes their origins, their catastrophic courses, and their consequences in both the short and long terms. The impacts of these epidemics ranged from the demographic--the "Spanish flu," for instance, claimed the lives of 6 percent of the country's population in six weeks--to the political, the social, the economic, the spiritual, the psychological, and the cultural. Moreover, as each of these epidemics occurred at crucial moments in the country's history--such as during the South African War and World War I--the book also examines how these processes affected and were affected by the five epidemics. To those who read this book, history will not look the same again."--Project Muse.